PENERAPAN MANAJEMEN MUTU TERHADAP KINERJA FINANSIAL DI INDUSTRI KREATIF: TINJAUAN LITERATUR SISTEMATIK - Subroto, Melvin Rahma Sayuga; Kuncoro, Andreas Mahendro; Ohara, Eric (Gapenas Publisher, 2024)
The creative industry faces challenges in balancing the need for standardization with the need for creativity. Standardization can improve efficiency and quality, but if it is too rigid, it can hinder creativity. This study uses the systematic literature review (SLR) method to explore this balance and its impact on financial performance. From the 18 articles analyzed, it was found that the implementation of flexible and adaptive quality management can improve efficiency without limiting creativity, and companies that manage to maintain this balance tend to produce better financial performance. Effective strategies include the development of adaptable quality standards, collaboration between human resources, and continuous feedback systems